Modification of bacterial cellulose to scaffold-like structures applied in process engineering - Kaźmierczak, Marta; Olejnik, Tomasz P.; Ogrodowczyk, Dominika; Kołodziejczyk, Marek (Lodz University of Technology Press, 2016)
Scaffolds are three-dimensional structures which provides necessary support for different cells’ vital functions. Although they are widely produced from different materials, most of them are not biodegradable. Bacterial bionanocellulose (BNC) has this property and additionally, has similar features to natural, extracellular matrixes. Unfortunately, natural channels which are in BNC’s structure have not sufficient diameter to colonize them with, for example, mammalian cells. Some experiments for pores enlargement in cellulose structure have been conducted. Multiple frosting and defrosting of properly prepared BNC’s samples has produced some positive results. Application the mixture of sterile vegetable oil and ethanol at the cultured layers of bionanocellulose gave expected results – diameter of the channels and chambers is enough to colonize them with viable cells. The results of described experiments give hope that bacterial bionanocellulose, because of its transformation’s simplicity, could be an alternative material for bioplastics productions.
Keywords: scaffolds; bionanocellulose; Gluconacetobacter xylinus; struktura; bionanoceluloza; Bakterie kwasu octowego